Characterization of the key aroma compounds in aged Zhenjiang aromatic vinegar by gas chromatography-olfactometry-mass spectrometry, quantitative measurements, aroma recombination and omission experiments. (October 2020) - Zhou, Zhilei; Jian, Dongzhen; Gong, Min; Zhu, Shenghu; Li, Guoquan; Zhang, Si; Zhong, Fang; Mao, Jian
Graphical abstract: Highlights: Aroma profile and odor-active compounds of aged ZAV were investigated. Higher caramel-like and buttery odor intensity was observed for aged ZAV. Twenty-seven odor-active compounds were perceived and sotolon was first detected. Odor activity values, aroma recombination and omission analysis were performed. Seven compounds were suggested as the most potent. Abstract: Zhenjiang aromatic vinegar (ZAV) is one of the most famous traditional Chinese cereal vinegars. The key aroma compounds in aged ZAV were characterized by gas chromatography-olfactometry-mass spectrometry (GC-O-MS), odor activity values (OAVs), aroma recombination and omission experiments. Sensory analysis revealed that higher odor intensity of caramel-like, buttery and overall complexity were observed for aged ZAV compared with fresh ZAV. A total of 68 compounds were quantitated, including 27 odorants with OAVs >1.0 in the aged ZAV. Sotolon was detected for the first time in Chinese cereal vinegars. Furthermore, the levels of 2, 3-butanedione, 2-methylpropanal, sotolon, dimethyl trisulfide, 3-hydroxy-2-butanone, 2, 4, 5-trimethyloxazole and tetramethylpyrazine changed significantly during the aging process. Aroma recombination revealed that the aroma profile of the aged vinegar could be closely simulated. Omission experiments demonstrated the important contributions of seven aroma compounds to the aged ZAV aroma, including 2, 3-butanedione, acetic acid, 2-methylpropanal, sotolon, 2, 4, 5-trimethyloxazole, 3-methylbutanoic acid and tetramethylpyrazine. This study indicates that the aging process substantially contribute to the overall aroma of ZAV.